DESIGN MODELING OF A UNIVERSITY'S COMPREHENSIVE-INTEGRATED SECURITY SYSTEM - Marina V. Dulyasova; Valeriy V. Markin (National Research Mordova State University, 2017)
Introduction: the safety of higher education institutions is considered to be of great importance nowadays. Security challenges need to be addressed through a comprehensive and integrative approach. This approach provides neutralisation of various threats systemically, risk prevention, minimisation of the tangible and moral harm. The project concept of "safe university" is proposed and substantiated for the above-mentioned purposes. Materials and Methods: the authors used a special literature survey on the issue, which is divided into three main groups of publications, where the complex security of educational institutions is considered in the context of the general theory of security, in the educational-methodical plan and within the framework of sociological, psychological and pedagogical approaches. The legislative and regulatory sources also indicated, legislative and regulatory legal acts reviews, "Safe City" concept, National standard "Information security technologies: complex and integrated ones. Standard requirements to architecture and technologies of intellectual systems of monitoring for safety of the companies and the territories" (State standard specification P 56875-2016), documents of higher education institutions, media reports. The analysis and generalisation of information was coupled with project modeling of the new comprehensive system of higher education institution security. Results: the authors introduce the concept, architecture and model of the comprehensive integrated higher education institution security, monitoring based on measures and indicators pertaining to implementation of standard requirements and level of satisfaction with safety, evaluation of the taken measures in terms of efficiency. Discussion and Conclusions: the main contours of the model for comprehensive integrated security system in a higher education institution and algorithm of interaction between the subjects are determined. These indicators allow measuring and estimating the efficiency of safety in a higher education institutions.